2021
DOI: 10.3390/toxins13090593
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Zearalenone Attenuates Innate Immune Responses and Suppresses NLRP3 Inflammasome Activation in LPS-Activated Macrophages

Abstract: Zearalenone (ZEA) is a mycotoxin that has several adverse effects on most mammalian species. However, the effects of ZEA on macrophage-mediated innate immunity during infection have not been examined. In the present study, bacterial lipopolysaccharides (LPS) were used to induce the activation of macrophages and evaluate the effects of ZEA on the inflammatory responses and inflammation-associated signaling pathways. The experimental results indicated that ZEA suppressed LPS-activated inflammatory responses by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…ZEN has been reported to have immunotoxicity in addition to its endocrine disrupting effects [31,32]. Previous reports indicated that ZEN exposure altered the hepatic cellular immune response, and suppressed the secretion of proinflammatory cytokines, such as IL-1, IL-6, and TNF-α [31][32][33]. Therefore, the negative regression trend between urinary ZEN and SAA concentrations obtained in the present study is possibly due to innate immune suppression of cows by low-level chronic ZEN exposure.…”
Section: Discussionsupporting
confidence: 57%
“…ZEN has been reported to have immunotoxicity in addition to its endocrine disrupting effects [31,32]. Previous reports indicated that ZEN exposure altered the hepatic cellular immune response, and suppressed the secretion of proinflammatory cytokines, such as IL-1, IL-6, and TNF-α [31][32][33]. Therefore, the negative regression trend between urinary ZEN and SAA concentrations obtained in the present study is possibly due to innate immune suppression of cows by low-level chronic ZEN exposure.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, food consumed as such, or after cooking processes, as well as water, may also contain internal or accidental components with a stimulating effect on NLRP3 inflammasome. Among these, mycotoxins (zearalenone, patulin, deoxynivalenol), trace metals (arsenic, cadmium), environmental and food contaminants (acrolein, 3-monochloropropane-1,2-diol, glycidol, and its esters), and acrylamide are few examples of NLRP3 activators, endowed with harmful inflammatory effects [ 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 ].…”
Section: Food and Nutraceuticals Components Bioavailability And Toxicitymentioning
confidence: 99%
“…The NLRP3 inflammasome is a vital part of the innate immune system and is composed of NLRP3, caspase-1 and apoptosis-associated speck-like protein containing CARD (ASC). Following recognition of PAMPs or DAMPs, the activation of NLRP3 inflammasome induces the maturation and release of proinflammatory cytokines, thereby triggering the progression of intestinal inflammation [19,20]. It is well known that the activation of NLRP3 inflammasome is often regulated by multiple intracellular signaling pathways, including nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK) complexes [21].…”
Section: Introductionmentioning
confidence: 99%